Perimortem caesarean section in COVID-19 era - Yudianto Budi Saroyo; Noroyono Wibowo; Damar Prasmusinto; Yuditiya Purwosunu; Rima Irwinda; Mohammad Adya Firmansha Dilmy; Angela Putri; Andrew Wijaya (Taylor & Francis Group, 2022)
AbstractCardiac arrest in pregnancy is very rare. Various methods have been proposed to return spontaneous circulation and prevent mortality, such as Perimortem Caesarean Section (PMCS). Since 2019, the COVID-19 pandemic has added to the difficulty in decision making and performing PMCS. Infection prevention being a priority due to the rapid spreading of the virus could cause hesitation upon initiating an emergency procedure, especially PMCS. We have reviewed the issues impacting on basic and advanced life support in adults with suspected or confirmed COVID-19.